The effect of cigarette smoking on the clinical outcome of pulmonary tuberculosis in Iraq - AL-Kadhimi, Hashim M.; Dawood, Haider N. (AL-Kindy College Medical Journal, 2014)
Background: Tobacco smoking and tuberculosis (TB) are two major public health problems; Associations between smoking and tuberculosis including death from tuberculosis have been reported , A reduction in smoking could be expected to have a significant impact on TB incidence and prevalence . Objectives: to assess the effect of smoking on tuberculosis. Methods: This study was conducted from June 2011 to June 2012 in 200 patients, adult ( aged 17 years and more), newly diagnosed patients of pulmonary tuberculosis, at the chest and Respiratory Disease Specialized Center in Baghdad. Demographic data, presenting symptoms, data on smoking, and recurrence of disease were compared. Information on smoking status, tobacco smoking was collected from patients using a specialized questionnaire. Smoking categories were grouped into ever for current / past smokers) and never. Results: A total of 200 patients with pulmonary tuberculosis, including 116 smokers and 84 non-smokers, were evaluated. The smokers were higher than non-smokers. Smokers were mostly male (p=0.001) there was statistically difference (P value = 0.05) for the duration of smoking, and for the number of cigarettes per day (p < 0.001). Regarding the symptoms of TB, there was statistically difference in occurrence of hemoptysis (P value 0.034) but there was no statistically difference between smokers and non-smokers in relapse rate. Conclusion: We conclude that smoking may increase the risk of pulmonary TB in men. The risk increase with increasing the duration of smoking and the number of cigarettes smoked. Hemoptysis significantly different with regard to the patients’ smoking status.